DETERMINAN PENDAPATAN ASLI DAERAH (PAD) DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Roni Sulaiman (2022)
This study aims to determine the effect of population, per capita income, investment and per capita expenditure on Regional Original Income (PAD) in all regencies/cities in the Special Region of Yogyakarta (DIY). The sampling in this study used a saturated sampling technique in 5 regions during 2013-2019, so a total sample of 35 data was obtained from the Central Statistics Agency (BPS). This study uses panel data analysis by combining time series data and cross section data. The results of the partial study indicate that the total population, per capita income, investment and per capita expenditure have a significant positive effect on regional original income (PAD).